Venous dysfunction in obstructive hypertrophic cardiomyopathies: Results from the "HCM-Vein" pilot study. (April 2023) - Réant, Patricia; Bonnet, Guillaume; Massie, Charles; Dezellus, Alexandre; Reynaud, Amélie; Michaud, Matthieu; James, Chloé; Constans, Joël; Lafitte, Stéphane
Abstract: Background: Hypertrophic cardiomyopathies (HCM) can be complicated by left ventricular outflow-tract obstruction (LVOTO) responsible for disabling exercise symptoms, a phenomenon influenced by hemodynamic factors including venous return. Methods: We aimed to evaluate venous dysfunction in obstructive HCM patients compared to healthy controls, and to investigate the relationship between venous dysfunction parameters and LVOTO in HCM. This is a clinical, monocentric, prospective, pilot study, in a tertiary care center. We investigated venous function using venous air plethysmography, and endothelial function. Results: Among the 30 symptomatic obstructive HCM patients, 30% (n = 9) presented abnormal venous residual volume fraction (RVFv) which translates in elevated ambulatory venous pressure vs. 0% in the 10 healthy controls (p < 0.05). Comparing obstructive HCM patients with abnormal RVFv (n = 9) to other obstructive HCM patients with normal RVFv (n = 21), there were no significant differences in terms of age, sex (67% male), and classical echocardiographic parameters both at rest and during exercise, except for left ventricular end-diastolic volume index which was significantly lower in the group with abnormal RVFv compared to the other HCM patients (40.1 ± 9.0 ml/m 2 vs. 50.2 ± 10.6 ml/m 2, p = 0.01). Fifty six percent of obstructive HCM patients with abnormal RVFv had an absolute increase in Willebrand factor ( vs. 26% of other obstructive HCM patients, p < 0.05). Conclusions: In this pilot monocentric study, venous insufficiency was observed in about 30% of symptomatic obstructive HCM patients. Patients with venous insufficiency had more frequently a smaller LV cavity volume. Due to the small sample size, this study is only hypothesis-generating, and further investigations are needed.